Insights into heterocyclization from two highly similar enzymes - McIntosh, John A. (2010)
[Image: see text] The cyanobactin biosynthetic pathways pat and tru, isolated from metagenomes of marine animals, lead to diverse natural products containing heterocycles derived from Cys, Ser, and Thr. Previous work has shown that PatD and TruD are extremely broad-substrate heterocyclase enzymes. These enzymes are virtually identical in their N-terminal putative catalytic domains, but only ~77% identical in their C-terminal putative substrate-binding domains. Here, we show that these differences allow the enzymes to control regioselectivity of posttranslational modifications, helping to control product chemistry in this hypervariable family of marine natural products.